The analysis of main stressors among high-stress primary school teachers by job positions: A nationwide survey in Japan - Tsubono, Kenjiro; Ogawa, Masaki (Frontiers in Public Health, 2022)
Objectives: A school teacher’s job is considered one of the most stressful occupations worldwide. To maintain the mental health of teachers, it is crucial to clarify the factors affecting work-related stress among teachers. The present study thus aimed to examine the main stressors among primary school teachers considering the difference in job positions by using data from a large-scale nationwide survey. Methods: We analyzed the data from a nationwide survey of public school teachers conducted between June and December 2021. The total number of participants was 138,651. The information of perceived main stressors, working hours per day, job workloads, job control, workplace support, and stress response scores were assessed by job position. Results: Among all teachers’ job positions, the working hours of vice-principals were the longest, but their stress response scores were the second lowest. In contrast, the stress response scores among diet and nutrition teachers and health education teachers were the highest; their supervisors’ and co-workers’ support scores were the lowest among all teachers. Quantitative and qualitative workloads, job control, workplace support from supervisors and co-workers are significantly associated with teachers’ stress responses in all job positions. Perceived main stressors among teachers were different depending on job positions. However, regardless of job positions, relationships with supervisors and co-workers were significantly associated with stress response scores among teachers. Dealing with difficult students and parents as well as workloads of clerical tasks were also associated with teachers’ stress responses depending on job positions. Conclusions: Perceived main stressors among teachers were different depending on job positions. However, relationships with supervisors and co-workers were significantly associated with stress response levels among teachers regardless of job positions. This study highlighted the importance of interpersonal relationships at the workplace in terms of teachers’ mental health. The results suggest that providing interpersonal skills training targeting co-workers’ relationships and harassment prevention measures would be crucial to maintain teachers’ mental health. The results also suggest that increasing school staff and providing sufficient organizational support for teachers will be required to prevent teachers’ burnout.